CREATIVE THINKING PROCESS IN STUDENT‘S SCIENTIFIC WORKS - Syahrin, Alfi; Dawud, Dawud; Suwignyo, Heri; Wahid, Abdul (Universitas Negeri Makassar, 2024)
This study aims to explain the process of creative thinking, including analytic, evaluative, applicative, and interpretative students in scientific work. The scientific works studied were in the form of Student Creativity Program, State University of Malang, Indonesia. This research uses a qualitative approach with a content analysis method. This research data in the form of paragraphs, paragraph clusters, and full text. The data source of this research is the scientific work of students. The research data collection technique was carried out by survey and documentation study. The process of data analysis is grouped into three stages, namely data reduction, data presentation, and drawing conclusions. The findings of this study indicate that the process of creative thinking in writing scientific papers can be done with four stages (1) the analytic stage in scientific work looks at the examination of arguments. (2) Evaluative in scientific work looks at the assessment of arguments in accordance with the topic of study. (3) Applicative in the work appears in arguing according to procedure. (4) Interpretations in scientific work appear in the clarification of meaning, so that the meaning conveyed is clear and directed. The findings of this study contribute to an author's understanding of the importance of using creative thinking processes in scientific writing. However, for further research it is recommended to examine the process of creative thinking with different objects.